A Perichoretic Model for Christian Love : A Theological Response to “A Common Word Between Us and You” - Ekaputra Tupamahu (Asosiasi Teolog Indonesia, 2013)
This article is basically a theological response to the Common Word Between Us and You. It gives a special emphasis on the Trinitarian concept of perichoresis and uses it as a model for Christian love in a pluralistic society. Close attention is given to Jurgen Moltmann’s social trinitarianism, and how it helps formulate a theological framework for a Christian attitude toward others.